Correlation of clinical and immunological data in a metastatic melanoma patient with heterogeneous tumor responses to ipilimumab therapy - Yuan, Jianda (Academy of Cancer Immunology, 2010)
Melanoma patients treated with anti-CTLA-4 have shown a range of anti-tumor responses. In this report, we describe the response of a single patient to anti-CTLA-4, with individual lesions disappearing, others stabilizing, and others progressing. These responses can be viewed as a clear manifestation of cancer immunoediting and its three phases of elimination, equilibrium and escape, with each tumor in this patient being at a discrete stage in the process. The patient's course and associated immunological monitoring and other laboratory data are presented in an immunogram, a way to visualize temporal associations between the multiple clinical and laboratory parameters.